Sistem Pendukung Keputusan Penentuan Wajib Pajak Berprestasi Menggunakan Metode Multi-Attribute Utility Theory dan Rank Order Centroid - Colin, Aldo Bahy; Ardiansah, Temi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Outstanding taxpayers based on the Bandar Lampung Mayor Decree in 2013 refer to individuals or business entities that demonstrate superior financial performance and high tax compliance. The problem experienced by the Bandar Lampung Regional Tax and Retribution Management Agency (BPPRD) is that the determination of outstanding taxpayers is calculated based on predetermined criteria. This study aims to apply the ROC method to determine the weight of criteria for determining outstanding taxpayers, and the MAUT method is used in alternative ranking of outstanding taxpayers so that the ranking results help and recommend to the Bandar Lampung BPPRD Office in determining outstanding taxpayers using criteria set by the Bandar Lampung BPPRD Office. The ranking results of outstanding taxpayers using the MAUT and ROC methods provide recommendations to the BPPRD Dina, namely rank 1 obtained with a value of 1.005 with the name of the taxpayer Bakso Sony Pagar Alam, rank 2 obtained with a value of 0.772 with the name of the taxpayer RM. Hang Dihi, and rank 3 obtained with a value of 0.776 with the name of the taxpayer Minang Indah.